101 Japanese idioms understanding Japanese language and culture through popular phrases - Maynard, Michael L.; Maynard, Senko K. 1945- (Passport Books, 1993)
This entertaining text offers a wealth of linguistic and cultural information for anyone studying Japanese, going to Japan, or in contact with Japanese friends or colleagues. Each idiom is accompanied by an explanation and then incorporated into a dialogue to illustrate the idiom's everyday use. For all students, this flexible book and audio program features 101 Japanese idiomatic and proverbial expressions that enrich student's knowledge of Japanese language and culture. Each left-hand page provides the expression in Japanese orthography and romanization, along with a whimsical illustration. Each right-hand page provides a literal translation of the idiom, its definition, cultural notes, and a dialogue in Japanese orthography, Roomaji, and English. Audiocassettes include expressive readings of the dialogues to help improve students' pronunciation